Bank Lending Rates and Financial Structure in Italy : A Case Study - Ferri, Giovanni (IMF Working Papers; Working Paper ;, 1995)
This paper discusses the relation between the financial structure and the determination of bank lending rates in Italy. It notes that the high degree of stickiness of bank lending rates observed in Italy in the past was related to constraints on competition within the banking and financial markets. In this light, it discusses the effect on the lending rate determination process of the sweeping financial liberalization process that characterized the last few years. The paper discusses also the role of the discount rate in speeding up the adjustment process of bank interest rates, and the pros and cons of its possible indexation. The empirical analysis is characterized by use of microeconomic (individual bank) data for a group of 63 Italian banks operating in locally different financial environments. This approach allows the identification of some aspects of the relation between financial structure and lending rate stickiness that were not highlighted in previous studies.